Guidelines for the treatment of head injury in adults - Firsching, Raimund; Rickels, Eckhart; Mauer, Uwe Max; Sakowitz, Oliver; Messing-Jünger, Martina; Engelhard, Kristin; Schwenkreis, Peter; Linn, Jennifer; Schwerdtfeger, Karsten (Journal of neurological surgery. Part A, Central European neurosurgery, 2017)
The workshop of scientific medical faculties (Arbeitsgemeinschaft wissenschaftlicher medizinischer Fakultäten [AWMF]) of Germany has asked societies of specific medical disciplines to jointly publish guidelines on the treatment of diseases and injuries. On behalf of the Deutsche Gesellschaft für Neurochirurgie, its commission on guidelines initiated an interdisciplinary approach to publish guidelines on the treatment of head injury in adults. These guidelines were published in German by the AWMF in late 2015. Because these guidelines have received widespread attention in Germany and became fundamental for research in head injuries, we have translated the German version into English to make it accessible to the international scientific community.